Indeks dan Tingkat Risiko Bahaya Longsor pada Ruas Jalan Nasional di Kabupaten Kerinci dan Kota Sungai Penuh, Provinsi Jambi - Mutiara Sari; Mona Foralisa Toyfur; Febrian Hadinata (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
The Regency of Kerinci and The City of Sungai Penuh are areas that prone to landslides. In 2021 and 2021, were 13 landslides on national road sections in both, which disrupted access to both areas. This study aims to calculate the index and determine the risk level of landslides on roads and bridges on national roads in both regions. Assessment methods and variables are taken based on the Guidelines for the Implementation of Risk Analysis for Natural Disasters Affecting Roads and Bridges. The index and risk level assessment are carried out by analyzing the risk factors for landslides, namely: hazard, exposure, vulnerability, external context, and capacity. The mapping of landslide risk based on Geographic Information Systems is based on scoring and weighting in all parameters, as well as overlays among all the constituent parameters. Based on the results of the study on ten national roads (with a total road length of 82.50 km) in the study area into two classes, namely: (a) low class (= 8.72%) on 7 roads located within the city, and (b) medium class (= 91.28%) on three roads connecting the cities.